Analysing the use of tools, initiatives, and approaches to promote sustainability in corporations. (2nd December 2019) - Lozano, Rodrigo
Abstract: Interest in sustainability from the corporate sector is evidenced by over 13, 000 companies in 160 countries that have signed the United Nations Global Compact. In this context, a number of tools, initiatives, and approaches (TIAs), e.g., circular economy, corporate social responsibility, eco‐efficiency, life cycle assessment, and sustainability reporting have been developed by and for corporations to engage and promote sustainability within their systems. Each of the TIAs has advantages when addressing sustainability issues and the company system's elements, but it has disadvantages in dealing with their complexities and interactions. Relying only on one TIA results in a limited contribution to sustainability, whereas using too many TIAs wastes resources and energy. The Corporate and Industrial Voluntary Initiatives for Sustainability (CIVIS) has been proposed to better combine the TIAs. A survey was developed to investigate the use of 24 TIAs. The survey was sent to a database of 5, 299 organisations (of which 3, 603 were companies), from which 202 responses were obtained. The responses were analysed using ratio analysis, principal component analysis, and cluster analysis. The responses show that some TIAs are well known and provide good results when used, for example, corporate social responsibility, corporate sustainability, and Global Reporting Initiative reports. The analyses show a number of groups of the TIAs that can help to better combine them. The paper updates the CIVIS framework in order to provide clearer guidance on how to combine the TIAs. A combination of between four and six initiatives appears to be most effective way to promote sustainability. The TIAs can help to promote sustainability in corporations, but they need to be combined correctly in order to address holistically the four dimensions of sustainability, the system elements, and stakeholders, while avoiding duplication of tasks and wasting resources.